The Degree in Rural Education and teacher training in the Mathematical Area - Analdino Pinheiro Silva Filho; Marco Antonio Leandro Barzano; Ludmila Oliveira Holanda Cavalcante (Universidade Federal do Norte do Tocantins, 2024)
This article discusses the initial training of rural teachers in the field of Mathematical, with reference to the Licentiate in Rural Education (LEDOC). For this, there is a broad survey in the literature of models of initial teacher training in rural areas, of the political and pedagogical aspects of LEDOC in Brazil and, in particular, of LEDOC of the Federal University of Recôncavo da Bahia (UFRB), in Brazil, Mathematical area. From the data, it is argued that the Brazilian LEDOC differs from many teacher training programs around the world, having the proposal claimed by the social movements of the field, a socially, politically and culturally referenced student profile and the pedagogical alternation, these being differentiating aspects. It was also found that the presence of graduates of the course has been triggering a rich process of knowledge production in Higher Education, pointing to ruptures with the mathematics worked on in conventional Degrees. However, some emerging challenges are considered, such as guaranteeing the pedagogical alternation and its effectiveness in the dimension of the teacher trainers' performance, in the construction of collective and interdisciplinary work, in the integralization of the activities of Tempo Universidade and Tempo Comunidade, as well as in the investment that is needed.